2020
DOI: 10.3390/su12051857
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Emotional Intelligence on Turnover Intention and the Moderating Role of Perceived Organizational Support: Evidence from the Banking Industry of Vietnam

Abstract: The objective of this study is to investigate the impact of emotional intelligence on turnover intention, noting the mediating roles of work-family conflict and job burnout as well as the moderating effect of perceived organizational support. Survey data collected from 722 employees at banks in Vietnam was analyzed to provide evidence. Results from the partial least squares structural equation modeling (PLS-SEM) using the SmartPLS 3.0 program indicated that there was a negative effect of emotional intelligence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
120
0
9

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3
1

Relationship

2
8

Authors

Journals

citations
Cited by 123 publications
(133 citation statements)
references
References 75 publications
(127 reference statements)
4
120
0
9
Order By: Relevance
“…Besides, the Durbin-Watson test indicated that d = 1.685 (1 < d <3), thus the authors concluded that the residues were independent of each other or they did not correlate between the residuals . Moreover, the VIF (Variance Inflation factor) magnification factor reached the maximum value of 2.123 (less than 5) and these independent variables are not closely related to each other, thus there was no multicollinearity (Giao et al, 2020). Note: BB = bank brand; IRP = interest rate policy; CON = convenience; SQ = service quality; EKA = employee knowledge and attitude; SDD = saving deposit decision; Gen = gender; Inc = income; Edu = educational level.…”
Section: Regression Analysismentioning
confidence: 99%
“…Besides, the Durbin-Watson test indicated that d = 1.685 (1 < d <3), thus the authors concluded that the residues were independent of each other or they did not correlate between the residuals . Moreover, the VIF (Variance Inflation factor) magnification factor reached the maximum value of 2.123 (less than 5) and these independent variables are not closely related to each other, thus there was no multicollinearity (Giao et al, 2020). Note: BB = bank brand; IRP = interest rate policy; CON = convenience; SQ = service quality; EKA = employee knowledge and attitude; SDD = saving deposit decision; Gen = gender; Inc = income; Edu = educational level.…”
Section: Regression Analysismentioning
confidence: 99%
“…Giao, et al [34] recommended that the quality of a PLS model should be assessed by R 2 value. They highlighted R 2 value of above 0.26 for a larger effect, ranging from 0.13 to 0.26 for a medium effect, and under 0.02 for a small effect.…”
Section: Model Fitmentioning
confidence: 99%
“…After the initial Cronbach's alpha analysis, EMR2 and AW4 were excluded because the correlations with the total variability were less than 0.3 (Giao, Vuong, Huan, et al, 2020). Subsequent tests indicated that the remaining measurement scales had high Cronbach's Alpha coefficients (> 0.7) with the correlation coefficient between items and total variability greater than 0.3 (Table 1).…”
Section: Personal Characteristics Of the Participantsmentioning
confidence: 99%